2021
DOI: 10.1111/imm.13425
|View full text |Cite
|
Sign up to set email alerts
|

Human immune polymorphisms associated with the risk of cryptococcal disease

Abstract: Cryptococcus neoformans is an opportunistic fungal pathogen that can cause lethal cryptococcal meningitis in immunocompromised individuals such as those with HIV/AIDS. In addition, cryptococcal infections occasionally arise in immunocompetent individuals or those with previously undiagnosed immunodeficiencies. The course of cryptococcosis is highly variable in both patient groups, and there is rapidly growing evidence that genetic polymorphisms may have a significant impact on the trajectory of disease. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…Related studies indicated that C. neoformans clinical isolates that were more easily phagocytosed by macrophages (termed high-uptake C. neoformans ) were associated with higher fungal burden in the brain 24 , 25 . Our previous study also suggested that C. neoformans with a high-uptake rate (HU) exhibited an increasing ability to disseminate to the brain than those with a low-uptake rate (LU), and this ability was associated with elevated type-2 cytokine production 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Related studies indicated that C. neoformans clinical isolates that were more easily phagocytosed by macrophages (termed high-uptake C. neoformans ) were associated with higher fungal burden in the brain 24 , 25 . Our previous study also suggested that C. neoformans with a high-uptake rate (HU) exhibited an increasing ability to disseminate to the brain than those with a low-uptake rate (LU), and this ability was associated with elevated type-2 cytokine production 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that cryptococcal infection of the bone is more common in patients with immune insufficiency, 2 , 3 including HIV infection 4 or serious immunodeficiency with long-term use of immunosuppressants, as well as diabetes, 5 sarcoidosis, 6 tuberculosis, 7 lymphopenia, 8 rheumatoid arthritis 9 and other related immunodeficiencies. In 1955, Eisen et al 10 reported a case of cryptococcosis with lung and spinal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, comparing TLR2 alleles (2180 C/T) across various patient groups failed to find statistically significant changes in their frequency [ 59 ]. TLR1 rs5743563 T/T, TLR2 rs3804099 T/T, TLR6 rs3796508 G/A, and TLR6 rs3804099 C/T were associated with a higher risk of cryptococcal meningitis in HIV-negative patients, whereas rs5743563 and rs3804099 were associated with CSF cytokine expression [ 60 ].…”
Section: Toll-like Receptorsmentioning
confidence: 99%